1999
DOI: 10.1136/hrt.82.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive pericarditis

Abstract: Background-Pericardial thickening is an uncommon complication of cardiac surgery. Objectives-To study pericardial thickening as the cause of severe postoperative venous congestion. Subjects-Two men, one with severe aortic stenosis and single coronary artery disease, and one with coronary artery disease after an old inferior infarction. Both had coronary artery bypass grafting surgery. Methods-Magnetic resonance imaging (MRI), Doppler echocardiography, and cardiac catheterisation.Results-Venous pressure was rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The finding of a peak right ventricular pressure of 85 mmHg lead us to search for concomitant myocardial disease, which could not be confirmed by myocardial biopsy. The haemodynamic profile of our cases is similar to those described by Henein et al, 6 who reported striking evidence of restrictive physiology in their two cases where the restriction was localized in the pericardium. They claimed that these cases should be considered as a distinct diagnostic entity, since the pathological basis and treatment are different from those needed for intrinsic myocardial disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding of a peak right ventricular pressure of 85 mmHg lead us to search for concomitant myocardial disease, which could not be confirmed by myocardial biopsy. The haemodynamic profile of our cases is similar to those described by Henein et al, 6 who reported striking evidence of restrictive physiology in their two cases where the restriction was localized in the pericardium. They claimed that these cases should be considered as a distinct diagnostic entity, since the pathological basis and treatment are different from those needed for intrinsic myocardial disease.…”
Section: Discussionsupporting
confidence: 89%
“…In the second case, however, the two first criterions were not met. Furthermore, significant pulmonary hypertension is not part of the known haemodynamic features of constrictive pericarditis, 6,12 instead being suggestive for restrictive cardiomyopathy. The finding of a peak right ventricular pressure of 85 mmHg lead us to search for concomitant myocardial disease, which could not be confirmed by myocardial biopsy.…”
Section: Discussionmentioning
confidence: 98%
“…Constrictive pericarditis is due to scarring which extends into the underlying myocardium and loss of elasticity of the pericardium, resulting in external impedance of cardiac filling. 17 Coronary artery and bypass graft occlusion, unstable angina and persistent pericardial pain have been described. The majority of patients respond to anti-inflammatory agents, and only a small proportion requiring pericardial drainage or pericardiectomy.…”
Section: Post Pericardiotomy Syndromementioning
confidence: 99%
“…Hemodynamic differences [1,4,17,27] include 1) respiratory variation of ventricular filling and ventricular interdependence, which are not present in restrictive cardiomyopathy; 2) RV and LV diastolic pressures elevated in both but, in restriction, diastolic pressure in the LV higher than the RV by at least 3 to 5 mm Hg; 3) the absolute level of atrial and ventricular diastolic pressure elevations usually higher in restrictive cardiomyopathy (> 25 mm Hg); 4) marked RV systolic hypertension (> 60 mm Hg) indicative of restriction; and 5) pulmonary hypertension common in restrictive cardiomyopathy and rare in constrictive pericarditis.…”
Section: Pathophysiologymentioning
confidence: 99%